Direct borohydride fuel cell performance using hydroxide‐conducting polymeric nanocomposite electrolytes. Issue 24 (30th January 2013) - Huang, Ching‐Chieh; Liu, Ying‐Ling; Pan, Wen‐Han; Chang, Chia‐Ming; Shih, Chao‐Ming; Chu, Heng‐Yi; Chien, Chun‐Hui; Juan, Cheng‐Hsin; Lue, Shingjiang Jessie
<x xml:space="preserve">Abstract</x> Solid electrolyte membranes based on alkali‐doped polyvinyl alcohol (PVA) and PVA/carbon nanotubes (PVA/CNTs) are used in direct borohydride fuel cells (DBFCs). As 0.05 wt % of CNT is incorporated into the PVA matrix, the polymer crystallinity is decreased from 42.4% to 38.0% and the fractional free volume increases from 2.48% to 3.53%. The KOH‐doped PVA/CNT exhibits the highest ionic conductivity of 0.0805 S cm−1, because of the increased polymer free volume (which promotes vehicular OH− transport) and the presence of CNT (which serves as the conducting microchannels). Sodium borohydride (NaBH4) in NaOH solution and potassium borohydride (KBH4) in KOH mixture are fed into the cells. The power density of the KBH4‐based DBFC is almost twice that of the NaBH4‐based DBFC (184 vs. 92 mW cm−2) due to less KBH4 permeability through the films, higher conductivity of the KOH‐doped PVA composites than those in the sodium counterpart, and probably higher electro‐catalytic kinetics. © 2013 Wiley Periodicals, Inc. J. Polym. Sci., Part B: Polym. Phys. 2013, 51, 1779–1789, 2013